DEVELOPMENT OF READING COMPREHENSION AT FUTURE NURSES (Scientific journal of the Fergana State University, 2024)
This study examined the effects of rhythm-based reading intervention for future nurses who demonstrated difficulties in the recognition of medical lexis. The intervention focused on fostering word reading via rhythm pace. The materials consisted of the 50 most well-known poems typically about anatomy of human body. The aims were to practice phonological recoding, consolidate anatomic representations of human body, and routinize reading process by rhythm paces. Compared to medical students (Pediatrics faculty) in randomly assigned to a control group, poor readers (students of Nursery faculty) in the treatment condition showed significant improvements in standardized measures of self-reading recoding, direct word recognition, and text-based reading comprehension after the one term’s intervention. The future nurses in the treatment condition also showed greater improvements in development of word recognition compared to medical students of Pediatrics faculty with efficient word recognition skills. The results provide evidence that a rhythm-based reading intervention is an effective ways to improve  low level of reading comprehension among medical workers, especially nurses.